2017
DOI: 10.1111/cdev.12785
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent Ethnic Identity in Social Context: A Commentary

Abstract: Key findings from the various studies of this special section of Child Development are that ethnic identity is embedded in a positive proximal interpersonal context in adolescence and that the links between ethnic identity and the interpersonal context seem to become stronger from the beginning of early adolescence on. Remarkably, the (longitudinal) studies do not show that ethnic identity is a better predictor of developmental outcomes or that it can be better predicted in minority groups than in majority gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…Rooted in ego‐identity theory (Erikson, 1968), developmental models have focused on understanding sequential processes through which youth come to develop a sense of belonging and commitment to an ethnic‐racial group. Process models draw attention to two key identity concepts: exploration and commitment (Marcia, 1966; Meeus, 2017; Phinney, 1989). Exploration is an individuals’ active search for information about the meaning of their group membership, whereas commitment or resolution is one’s sense of clarity about what their ethnic‐racial group means to them (Phinney, 1989).…”
Section: Ethnic‐racial Identity Vis‐à‐vis Ethnic‐racial Discriminatiomentioning
confidence: 99%
“…Rooted in ego‐identity theory (Erikson, 1968), developmental models have focused on understanding sequential processes through which youth come to develop a sense of belonging and commitment to an ethnic‐racial group. Process models draw attention to two key identity concepts: exploration and commitment (Marcia, 1966; Meeus, 2017; Phinney, 1989). Exploration is an individuals’ active search for information about the meaning of their group membership, whereas commitment or resolution is one’s sense of clarity about what their ethnic‐racial group means to them (Phinney, 1989).…”
Section: Ethnic‐racial Identity Vis‐à‐vis Ethnic‐racial Discriminatiomentioning
confidence: 99%
“…These patterns did not emerge for other ethnic groups. The authors of these studies concluded that identifying with a stigmatized ethnic group – one that is at the center of many United States immigration debates – may lead to personally and/or socially destructive behavior because the individual may be blocked from pursuing more prosocial endeavors (see Meeus, 2017, for a review of similar general principles regarding the adaptiveness of ethnic identity). Further, in the United States, many media images have portrayed Hispanics as drug dealers and users and as sexually promiscuous, perhaps leading Hispanic youth to identify with these stereotypes (Mastro, Behm-Morawitz, & Kopacz, 2008).…”
Section: Ethnic and National Identity Among Immigrant Youthmentioning
confidence: 99%
“…Some advances in identity theorizing may be useful to further expand the investigation of ethnic and national identity, and their intersection with personal identity, among immigrants. Among these are addition of a reconsideration dimension for ethnic and national identity (Meeus, 2017). Within the personal identity literature, reconsideration refers to reevaluating current commitments and deciding whether to retain, suspend, or discard them (Crocetti, 2017).…”
Section: The Intersections Among Ethnic National and Personal Identit...mentioning
confidence: 99%
“…Even those conceptualizations, which have emphasized the distinction between different identity processes (e.g., Phinney & Ong, 2007; Umaña-Taylor, et al, 2004), still did not take into account different modes of identity processes (e.g., exploration as happening through in-depth exploration and reconsideration of commitments; Syed et al, 2013). Such situation has resulted in a limited picture of identity development among ethnic minority youth in terms of identity processes and developmental cycles (Meeus, 2017; Syed et al, 2013).…”
Section: Identity As a Developmental And Acculturative Taskmentioning
confidence: 99%